Sea Ice Meltwater and Circumpolar Deep Water Drive Contrasting Productivity in Three Antarctic Polynyas. Issue 5 (2nd May 2019) - Moreau, S.; Lannuzel, D.; Janssens, J.; Arroyo, M. C.; Corkill, M.; Cougnon, E.; Genovese, C.; Legresy, B.; Lenton, A.; Puigcorbé, V.; Ratnarajah, L.; Rintoul, S.; et al.
Abstract: In the Southern Ocean, polynyas exhibit enhanced rates of primary productivity and represent large seasonal sinks for atmospheric CO2 . Three contrasting east Antarctic polynyas were visited in late December to early January 2017: the Dalton, Mertz, and Ninnis polynyas. In the Mertz and Ninnis polynyas, phytoplankton biomass (average of 322 and 354 mg chlorophyll a (Chl a )/m 2, respectively) and net community production (5.3 and 4.6 mol C/m 2, respectively) were approximately 3 times those measured in the Dalton polynya (average of 122 mg Chl a /m 2 and 1.8 mol C/m 2 ). Phytoplankton communities also differed between the polynyas. Diatoms were thriving in the Mertz and Ninnis polynyas but not in the Dalton polynya, where Phaeocystis antarctica dominated. These strong regional differences were explored using physiological, biological, and physical parameters. The most likely drivers of the observed higher productivity in the Mertz and Ninnis were the relatively shallow inflow of iron‐rich modified Circumpolar Deep Water onto the shelf as well as a very large sea ice meltwater contribution. The productivity contrast between the three polynyas could not be explained by (1) the input of glacial meltwater, (2) the presence of Ice Shelf Water, or (3) stratification of the mixed layer. Our results show that physical drivers regulate the productivity of polynyas, suggesting that the response of biological productivity and carbon export to future change will vary among polynyas. Key Points: In summer 2016–2017, phytoplankton biomass and NCP in the Mertz and Ninnis polynyas were 3 times those measured in the Dalton polynya Iron‐rich Circumpolar Deep Water and sea ice meltwater best explained this productivity contrast. The productivity contrast between the three polynyas could not be explained by the meteoric water, the Ice Shelf Water, or stratification